Macroinvertebrate Assemblages along the Longitudinal Gradient of an Urban Palmiet River in Durban, South Africa - Jeffrey Lebepe; Ntombifuthi Khumalo; Anele Mnguni; Sashin Pillay; Sphosakhe Mdluli (Biology, 2022)
Urban rivers are regarded as unnatural because they drain catchments characterized by impervious surfaces. The present study explored macroinvertebrate communities in relation to water and habitat quality along the longitudinal gradient of an urban Palmiet River in Durban, South Africa. Sampling was conducted across six sites along the river. The water quality has shown a significant variation (ANOVA, p < 0.05) across six sites. Good-quality water was observed at Site 6, whereas Site 5 exhibiting hypertrophic condition. Sites 4 to 1 were all eutrophic; however, nutrient levels showed to decrease from Site 4 down to Site 2 and increased again at Site 1. A similar trend was observed for habitat quality, with Site 6 showing excellent and Site 5 exhibited poor habitat. Coinciding with water and habitat quality, macroinvertebrate diversity and abundance showed significant differences across six sites. Sensitive palaemonids, notonemourids, and amphipods were only observed in the headwaters and have contributed over 50% of the variation in abundance between Site 6 and other sites. The non-metric multidimensional scaling (NMDS) plot has also shown clear discrimination (MANOVA, p < 0.001) for the Average Score Per Taxon (ASPT) across the six sites. Macroinvertebrate communities have shown a clear association between water and habitat quality. These findings affirm the ecological importance of urban rivers as they provide refuge to aquatic biodiversity, with anthropogenic litter providing additional habitats for other taxa. Despite the current conditions supporting biodiversity and the functioning of the river, it is unclear if the system could endure further disturbance.